2019
DOI: 10.1080/1369183x.2018.1550157
|View full text |Cite
|
Sign up to set email alerts
|

Economic conditions, group relative deprivation and ethnic threat perceptions: a cross-national perspective

Abstract: Explaining negative attitudes towards immigration in general and threat due to immigration, in particular, has been a major topic of study in recent decades. While intergroup contact has received considerable attention in explaining ethnic threat, group relative deprivation (GRD), that is, feelings that one's group is unfairly deprived of desirable goods in comparison to relevant out-groups, has been largely ignored in cross-national research. Nevertheless, various smaller-scale studies have demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 68 publications
3
66
0
Order By: Relevance
“…Additionally, we applied longitudinal analyses, a necessary strategy for tentative claims of causal connections over time. Future studies could extend the current framework by including other social‐psychological underpinnings of far‐right support, such as perceived relative deprivation (e.g., Meuleman, Abts, Schmidt, Pettigrew, & Davidov, ; Walker & Pettigrew, ), collective narcissism (de Zavala et al, ; Marchlewska, Cichocka, Panayiotou, Castellanos, & Batayneh, ), restricted intergroup contact (Knowles & Tropp, ; Pettigrew, ), and political cynicism (e.g., Van Assche et al, ; Van Assche, Van Hiel, Dhont, & Roets, ), and by examining the unique effects of these predictors in a single and unified model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we applied longitudinal analyses, a necessary strategy for tentative claims of causal connections over time. Future studies could extend the current framework by including other social‐psychological underpinnings of far‐right support, such as perceived relative deprivation (e.g., Meuleman, Abts, Schmidt, Pettigrew, & Davidov, ; Walker & Pettigrew, ), collective narcissism (de Zavala et al, ; Marchlewska, Cichocka, Panayiotou, Castellanos, & Batayneh, ), restricted intergroup contact (Knowles & Tropp, ; Pettigrew, ), and political cynicism (e.g., Van Assche et al, ; Van Assche, Van Hiel, Dhont, & Roets, ), and by examining the unique effects of these predictors in a single and unified model.…”
Section: Discussionmentioning
confidence: 99%
“…The original response options were 1 = 'Yes, several', 2 = 'Yes, a few' and 3 = 'No, none'. We recoded this variable so that higher values indicated more contact (for a more detailed examination of the contact effect, see Green et al 2018, andMeuleman et al 2018, in this volume). Since the extent of media consumption in the form of watching TV may also explain negative attitudes towards Muslim immigrants (Popescu et al 2015), we controlled for individual TV exposure as well.…”
Section: Control Variablesmentioning
confidence: 99%
“…This perceived deprivation was associated with group‐based feelings of anger, in turn promoting greater engagement in political action against government redress for Aboriginal Australians. More recently, Meuleman, Abts, Schmidt, Pettigrew, and Davidov () found that group RD by Europeans was associated with perceived ethnic threat. In a similar vein, Bagci, Stathi, and Piyale () found that, in a high conflict intergroup context (disadvantaged Kurds and advantaged Turks), imagined contact with the disadvantaged group increased both collective active tendencies and, marginally, perceptions of RD among members of the advantaged group.…”
Section: Introductionmentioning
confidence: 99%